2005
DOI: 10.1111/j.1365-2249.2006.02999.x
|View full text |Cite
|
Sign up to set email alerts
|

Age dependency and mutual relations in T and B lymphocyte abnormalities in common variable immunodeficiency patients

Abstract: Summary Common variable immunodeficiency (CVID) islymphocytes, showed age dependency to be more significant than in the control group. Our study demonstrates that T and B lymphocyte abnormalities in CVID are partially related to each other. Some of those abnormalities are not definite, but may evolve with age of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 28 publications
7
33
1
Order By: Relevance
“…These abnormalities include an increase in HLA-DR, CD29, CD45RO, and CD95 (APO-1/Fas) and a decrease in CD27, CD45RA, and CD62L, especially in patients with increased CD21 low B-cell counts and decreased memory and regulatory B-cell counts [25,44]. CVID patients present with both low regulatory B cell counts and increased IFN-γ + TNF-α + CD4…”
Section: Activated Cd4 + T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…These abnormalities include an increase in HLA-DR, CD29, CD45RO, and CD95 (APO-1/Fas) and a decrease in CD27, CD45RA, and CD62L, especially in patients with increased CD21 low B-cell counts and decreased memory and regulatory B-cell counts [25,44]. CVID patients present with both low regulatory B cell counts and increased IFN-γ + TNF-α + CD4…”
Section: Activated Cd4 + T Cellsmentioning
confidence: 99%
“…Traditionally, the T-cell abnormalities that characterize CVID included a reduced T-cell count, decreased lymphocyte proliferation in response to mitogens and antigens, defective T-cell signaling, decline of regulatory T cell (Tregs) counts, uncontrolled T-cell polarization, elevated levels of T-cell activation markers, and abnormality in cytokine production secondary to gene polymorphisms [12][13][14][21][22][23][24][25][26].…”
Section: T-cell Abnormalities In Cvidmentioning
confidence: 99%
“…Although various abnormalities in number and function of T cells (3)(4)(5)(6)(7), B cells (8)(9)(10)(11)(12)(13), and dendritic cells (14)(15)(16) have been described, the immunopathological mechanism leading to disturbed Ab production in CVID patients has not yet been defined.…”
Section: Ommon Variable Immunodeficiency (Cvid) Is a Clinically Hetmentioning
confidence: 99%
“…Previous studies have shown abnormalities in B cell subset composition -a diminution in memory B cells and increase in naive follicular (FO) B cells (5). Naive FO B cells IgM pos CD27 neg (17,18) constitute a major B cell subset in the peripheral blood of patients with CVID.…”
Section: Ommon Variable Immunodeficiency (Cvid) Is a Clinically Hetmentioning
confidence: 99%
“…(2). Several research groups have found correlations between B-cell compartment abnormities and clinical presentations (1,3,4); however, the causal relationship between the defective B-cell function and the clinical picture is still elusive.…”
mentioning
confidence: 99%